Manipulating atomic defects in plasmonic vanadium dioxide for superior solar and thermal management - Ke, Yujie (2021)
Vanadium dioxide (VO2) is a unique active plasmonic material due to its intrinsic metal-insulator transition, remaining less explored. Herein, we pioneer the method to tailor the VO2 surface plasmon by manipulating its atomic defects and establish a universal quantitative understanding based on seven representative defective VO2 systems. The record high tunability is achieved for the localized surface plasmon resonance (LSPR) energy (0.66–1.16 eV) and transition temperature range (40-100 oC). Drude model and density function theory reveal the charge of cations plays a dominant role over the numbers of valence electrons to determine the free electron concentration. We further demonstrate their superior performances in extensive unconventional plasmonic applications including energy-saving smart windows, wearable camouflage devices, and encryption inks.